2011
DOI: 10.1063/1.3662927
|View full text |Cite
|
Sign up to set email alerts
|

Phase separation in strained epitaxial InGaN islands

Abstract: Phase separation (PS) produces InN composition gradients in InGaN islands, which may be important for light emitting diodes, solar cells, and lasers. Thus, the control of PS is critical, and the kinetic growth process, which is suggested to be important for controlling PS in Stranski-Krastanov islands, becomes a key factor in producing materials for optoelectronic devices. We present atomistic-strain-model Monte Carlo simulations for PS in strained epitaxial InGaN islands. Our simulations illustrate how the PS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 22 publications
1
16
0
Order By: Relevance
“…Theoretically, it was found that indium distribution in InGaN/GaN islands strongly depends on subsurface diffusion, whereby indium atoms tend to occupy the outmost island surface layer. 25 Thus, the island-like surface morphology together with the strain relaxation of the grown (0001) InGaN layers (<750 C) were attributed to the enhanced In incorporation, while the constant surface morphology of the ð11 22Þ InGaN layers did not induce a significant change in compositional trend.…”
Section: B Composition and Crystalline Propertiesmentioning
confidence: 98%
“…Theoretically, it was found that indium distribution in InGaN/GaN islands strongly depends on subsurface diffusion, whereby indium atoms tend to occupy the outmost island surface layer. 25 Thus, the island-like surface morphology together with the strain relaxation of the grown (0001) InGaN layers (<750 C) were attributed to the enhanced In incorporation, while the constant surface morphology of the ð11 22Þ InGaN layers did not induce a significant change in compositional trend.…”
Section: B Composition and Crystalline Propertiesmentioning
confidence: 98%
“…The most promising candidate for building a path across the green LED field is expected to be In x Ga 1Àx N. Alloying GaN with InN enables the development of a platform with combined blue and green LEDs based on a homogeneous system. However, the required indium content of at least 25% in alloys 1 leads to defect formation 2 and subsequent deterioration of electrical properties and decrease of device efficiency. On the other hand, the adjustable direct band gap and exceptional resistance to irradiation damage enable the application of In x Ga 1Àx N in solar cells for outer space.…”
Section: à3mentioning
confidence: 99%
“…Thus, In clustering introduced at surfaces during growth cannot be excluded. Indeed, previous simulations indicate that phase separation in InGaN islands depends strongly on the surface and subsurface kinetics . Furthermore, bulk kinetics may play a significant role in suppressing or restricting the size of InN clusters in the case of plastically relaxed InGaN epilayers.…”
Section: Discussionmentioning
confidence: 96%